INDEPENDENSI PENGAWASAN TERHADAP BANK BADAN USAHA MILIK NEGARA (BUMN) DALAM SISTEM HUKUM NASIONAL DI INDONESIA - Shandy Utama, Andrew (Soumatera Law Review, 2018)
Bank position as a financial institution whose business activities collect funds from the community and channel the funds back to the community, and provide financial services. Based on its ownership, the bank is divided into private / private owned banks and state-owned banks, or better known as State-Owned Enterprises (SOEs). The problem in this research is how to supervise BUMN bank in national banking system? What is the government and the House of Representatives intervention on state-owned banks? How is the independence of oversight of state-owned banks after the enactment of Law Number 21 Year 2011? The method used in this research is normative legal research by using approach of legislation. The result of this research is that supervision of state-owned banks in the national banking system is implemented by Bank Indonesia as central bank, but under government intervention as shareholder and House of Representatives as supervisor of government policy. Following the enactment of Law Number 21 of 2011, the supervision of state-owned banks was handed over to the Financial Services Authority as an independent state institution. So that will provide legal certainty for the parties.